School-based physical activity and health-related fitness in Mediterranean students: findings from the DELICIOUS project - Aly, Mohamed; Ammar, Achraf; Trabelsi, Khaled; Masmoudi, Liwa; El-Gyar, Noha; Shalaby, Amira M.; Abdelkarim, Osama (Frontiers in Public Health, 2025)
BackgroundPhysical inactivity among children is a growing public health concern, particularly in Mediterranean countries, where lifestyle changes have contributed to declining physical fitness levels. Structured school-based interventions have shown promise in improving children’s health-related physical fitness (HRF), but cross-cultural differences in intervention effectiveness remain understudied. This study, conducted within the DELICIOUS project, evaluates the impact of a standardized physical activity (PA) intervention on HRF components among children (8–10 years) and early adolescents (11–14 years) from five Mediterranean countries: Egypt, Italy, Lebanon, Portugal, and Spain.MethodsA total of 937 participants aged 8–14 years took part in a six-month school-based PA program designed to enhance speed, agility, muscular strength, cardiovascular endurance, and coordination. Physical fitness was assessed using the International Physical Performance Test Profile (IPPTP) before and after the intervention. A three-way repeated measures ANOVA (Time × Age × Country) assessed intervention effects on anthropometric and fitness variables, while a two-way ANOVA (Age × Country) examined the percentage changes in these HRF across age groups and countries.ResultsSignificant improvements were observed across multiple health-related fitness components, particularly in speed, lower-body power, coordination, muscular endurance, and cardiovascular endurance. Early adolescents (11–14 years) generally showed greater gains than younger children (8–10 years). The magnitude of improvement in fitness outcomes varied by country. Lebanon and Portugal recorded the most substantial gains in sprint, strength, and endurance. Spain and Italy showed relatively smaller improvements, especially among younger participants, whereas Egyptian students demonstrated notable gains in sprint performance and endurance, particularly among early adolescents, along with the most significant BMI reduction observed in the study. BMI remained stable across participants, suggesting that fitness improvements were achieved alongside healthy growth, without adverse changes in body composition.ConclusionA structured PA intervention can effectively improve HRF in children across Mediterranean countries, though outcomes vary by age and cultural context. These findings highlight the need for tailored, school-based PA programs that consider baseline fitness levels and regional factors. Implementing such interventions could play a crucial role in addressing physical inactivity and fostering long-term health benefits in children.